BIOLOGICAL EFFECTIVENESS OF FUNGICIDES AGAINST RICE BLAST IN THE REPUBLIC OF KARAKALPAKSTAN - G.K.Reipova; H.H.Nuraliev (EPRA International Journal of Research and Development (IJRD), 2023)
The article presents data on the study of the use of fungicides against rice blast in the Republic of Karakalpakstan. The fungicide Foliant BT, 22.5% с.e., showed the highest biological effectiveness against rice blast. (a.i. - Tebuconazole + triadimefon), which was 90.0-92.7%, and the yield was 68.7 t/ha. Then came the drug Amistar Top 32.5% s.c., taken as a standard, where the efficiency was 86.5-88.9%, with a yield of 64.2 t/ha, followed by the fungicide Merit 32.5% s.c. comparable with the standard. (a.i. - Azoxystrobin + Difenoconazole), where the biological efficiency was 85.8-87.1% with a yield of 66.5 t/ha.